2013
DOI: 10.1002/jbmr.1956
|View full text |Cite
|
Sign up to set email alerts
|

Risk assessment tools to identify women with increased risk of osteoporotic fracture: Complexity or simplicity? A systematic review

Abstract: A huge number of risk assessment tools have been developed. Far from all have been validated in external studies, more of them have absence of methodological and transparent evidence, and few are integrated in national guidelines. Therefore, we performed a systematic review to provide an overview of existing valid and reliable risk assessment tools for prediction of osteoporotic fractures. Additionally, we aimed to determine if the performance of each tool was sufficient for practical use, and last, to examine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
134
0
8

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 163 publications
(142 citation statements)
references
References 112 publications
(228 reference statements)
0
134
0
8
Order By: Relevance
“…Recently developed prediction tools, such as the FRAX algorithm, Qfracture and Garvan Fracture Risk Calculator, are aimed to assist clinicians in the management of their patients through the calculation of the patient's 5-or 10-year risk of fracture based on a combination of known risk factors. 1 Although relying on observational data rather than intervention studies, the tools may also be useful to some extent in patient consultations to assist discussions on the impact of changing modifiable risk factors. 87 The difficulty in adequately predicting fracture risk after intervention is reflected in the current debate surrounding the accuracy of risk estimation once intervention with anti-osteoporotic drugs has taken place.…”
Section: Risk Assessment Tools and Reversibility Of Riskmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently developed prediction tools, such as the FRAX algorithm, Qfracture and Garvan Fracture Risk Calculator, are aimed to assist clinicians in the management of their patients through the calculation of the patient's 5-or 10-year risk of fracture based on a combination of known risk factors. 1 Although relying on observational data rather than intervention studies, the tools may also be useful to some extent in patient consultations to assist discussions on the impact of changing modifiable risk factors. 87 The difficulty in adequately predicting fracture risk after intervention is reflected in the current debate surrounding the accuracy of risk estimation once intervention with anti-osteoporotic drugs has taken place.…”
Section: Risk Assessment Tools and Reversibility Of Riskmentioning
confidence: 99%
“…1 However, many risk factors for osteoporosis and osteoporotic fractures are in themselves modifiable and such risk factors are potential targets for intervention. 2 However, the strongest risk factors such as age, family history and prior fracture are essentially nonmodifiable; therefore, osteoporosis drugs of course remain essential in managing patients with high fracture risk due to osteoporosis.…”
Section: Introduction and Aimmentioning
confidence: 99%
“…The OST scores were categorized with the cut-off value of 2; the BMD was normal if the OST score was ≥2, and low if the OST score was <2. (8,11,12) …”
Section: Auc Aucmentioning
confidence: 99%
“…In spite of this, both meta-analytic studies and systematic reviews have shown that the sensitivity of these tools is not higher than or equal to that of OST. (11,12) Furthermore, the performance of OST does not show consistent results, its sensitivity being higher than its specificity or vice versa. (13) The present study was carried out to evaluate the performance of OST in a more specific manner i.e.…”
Section: Introductionmentioning
confidence: 99%
“…The recent development of fracture prediction tools is a prime example of one clinical application of powerful statistical methods. (1) When prediction of an event is the sole objective, the existence of an association-whether causal or not-may be sufficient. However, to understand how that association arises, and to intervene appropriately, requires a deeper understanding of the cause and effect relationships.…”
mentioning
confidence: 99%